2007
DOI: 10.1152/ajpheart.00326.2006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for enhanced eNOS function in coronary microvessels during the second window of protection

Abstract: Nitric oxide (NO) derived from endothelial NO synthase (NOS) (eNOS) has been identified as a trigger for the second window of protection (SWOP), but its role as a mediator during the SWOP is a matter of debate. Eighteen mongrel dogs were chronically instrumented to measure left ventricular function, coronary blood flow, and wall thickening. Myocardial preconditioning was induced by 10 min coronary artery occlusion. After 24 h of reperfusion (during the SWOP), the hearts were excised. Coronary microvessels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…The baseline and post-isoflurane values for systemic hemodynamic and myocardial variables are consistent with previous findings in conscious instrumented dogs in a relaxed state. [24][25][26] The hemodynamic findings during isoflurane administration in the present study conform to previous work in canine models, which have indicated that 1 MAC isoflurane causes hypotension and has negative inotropic and coronary vasodilating effects. 25,27,28 Coronary vasodilation was suggested by an uncoupling of coronary blood flow from the prevailing myocardial oxygen demands, with the result that coronary venous PO 2 increased markedly.…”
Section: Discussionsupporting
confidence: 90%
“…The baseline and post-isoflurane values for systemic hemodynamic and myocardial variables are consistent with previous findings in conscious instrumented dogs in a relaxed state. [24][25][26] The hemodynamic findings during isoflurane administration in the present study conform to previous work in canine models, which have indicated that 1 MAC isoflurane causes hypotension and has negative inotropic and coronary vasodilating effects. 25,27,28 Coronary vasodilation was suggested by an uncoupling of coronary blood flow from the prevailing myocardial oxygen demands, with the result that coronary venous PO 2 increased markedly.…”
Section: Discussionsupporting
confidence: 90%
“…Two distinct windows of preconditioning cardioprotection have been previously described: an early phase of cardioprotection and a late phase or second window of protection (SWOP) (Bell and Yellon, 2001;Bolli, 2007;Kim et al, 2007). In Fig.…”
Section: Discussionmentioning
confidence: 97%
“…pGz applied to rats has been shown to produce vasodilatation, increase eNOS expression and increases its phosphorylation Wu et al, 2009). eNOS has been shown to be cardioprotective (Kim et al, 2007;Rastaldo et al, 2007;Szelid et al, 2010;Talukder et al, 2010). Thus, pGz has the potential to provide preconditioning cardioprotection in an in-vivo animal model of regional ischemia reperfusion (I/R) injury, such as acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…140 Vice versa, delayed ischemic preconditioning 24 hours before the sustained myocardial ischemia/reperfusion increases the activity of endothelial nitric oxide synthase, which mediates preservation of coronary vasodilator response to acetylcholine, carbachol, and bradykinin. 141,142 Reactive oxygen species formation, although detrimental acutely for endothelium-dependent coronary vasodilation in response to acetylcholine, is mandatory for the delayed protection by ischemic preconditioning. 143 Ischemic preconditioning not only preserves endothelium-dependent 88 Copyright ©1995, the American Physiological Society.…”
Section: Coronary Vascular Protection By Ischemic Preconditioningmentioning
confidence: 99%